Analisis Dinamika Atmosfer Saat Hujan Lebat di Wilayah Pontianak Menggunakan Model WRF-ARW (Studi Kasus 22-23 Desember 2022) - Andi Ihwan; Minuk Hidayatul Mabriyah; Randy Ardianto (Institut Teknologi Bandung, 2025)
Abstract West Kalimantan has a tropical rainforest climate characterized by high rainfall intensity. On December 22–23, 2022, heavy rainfall occurred in Pontianak City with an intensity reaching 101.3 mm/day, resulting in flooding in the area. This study analyzes weather conditions and atmospheric stability during the event using the WRF-ARW model with FNL data as model input, along with GSMaP data and observations of air temperature and surface pressure for verification. Model accuracy was evaluated using dichotomous equations (Accuracy, FAR, POFD), correlation coefficient, and Mean Absolute Error (MAE). The verification results indicate that the GD scheme performed better than the KF Kessler and KF Lin schemes, with the GD scheme achieving an accuracy value of 0.74 and lower error. Analysis using the GD scheme suggests atmospheric conditions conducive to the formation of convective clouds that caused the heavy rainfall. These conditions were marked by an unstable atmosphere with a maximum temperature of 30°C before the rain, low surface pressure, high wind speeds in the waters west of Pontianak City, humidity reaching 100%, and CAPE values indicating moderate instability (2000 J/kg). Keywords: Heavy rain, cumulus parameterization scheme, WRF-ARW